Impact of innovation on economic growth of Sri Lanka: an empirical study - Washima, M.N.F. (Faculty of Management Studies & Commerce, University of Jaffna, 2019)
Innovation is one of the most important factor and main incentive for sustainable growth and economic development of a country. This research aims to identify the impact of innovation and other macroeconomic variable on economic growth of Sri Lanka over the period of time 1978 to 2017. This research has used Ordinary Least Square Model (OLS) to identify the relationship between the innovation and Gross Domestic Product. According to the results, Research and Development expenditure, Patten Applications for residents, Gross Domestic Product per Capita, and capital formation are statistically and significantly influenced on economic growth of Sri Lanka. But, there is negative relationship between the Gross Domestic Product and export, expenditure education and Foreign Direct Investment. Hence, this study concludes that effectiveness of innovation will lead to sustainable economic growth of Sri Lanka. This study suggests that higher expenditure on scientific research and development and vocational and technical education may promote the productivity through new technology and innovations. And also, Policy makers should focus on promoting the monetary policy and allocating recourse efficiently for the sustainable growth of the country.
Keywords: Economic growth; gross domestic product; innovation; r&d expenditure